Letter to Rita Dobson from Dorothy O'Donnell - Dorothy O'Donnell:::::: (1976)
This letter is from the Camarillo Business and Professional Women's Club to Rita Dobson, Political Promotion Chairman. The club states that Jane Tolmach, a member of the Oxnard BPW, is a candidate for the California State Assembly from the 36th District. The Camarillo BPW members formally support her candidacy. They also recommend that the California State Federation of BPW endorse and support Mrs. Tolmach. The letter is signed by Dorothy O'Donnell, Legislation Chairman, with a copy sent to Jane Tolmach.